Effects of drought stress induced by D-Mannitol on the germination and early seedling growth traits, physiological parameters and phytochemicals content of Tunisian squash (Cucurbita maximaDuch.) landraces - Saadaoui, Wassim; Tarchoun, Neji; Msetra, Insaf; Pavli, Ourania; Falleh, Hanen; Ayed, Chadha; Amami, Roua; Ksouri, Riadh; Petropoulos, Spyridon A. (Frontiers in Plant Science, 2023)
Drought stress is one of the most devastating environmental stressors, especially in the arid and semiarid regions of the world. Considering the major constraints that drought stress poses to crop production and the consequent yield losses in food crops, breeding for climate-resilient crops is an efficient means to mitigate stress conditions. This study aimed at evaluating the response of four squash (Cucurbita maxima Duchesne) landraces to drought stress at germination and at plant stage. Drought stress was induced by different concentrations of D-mannitol (-0.24, -0.47 and -0.73 MPa). The tested parameters at germination stage included germination percentage, seedling vigor index, seed water absorbance and seedling growth potential. At the plant stage, leaf chlorophyll and carotenoids content, chlorophyll fluorescence, evapotranspiration, photosynthesis activity and several biomarkers, namely malondialdehyde, proline, total phenols content, total flavonoids content and DPPH radical scavenging activity were evaluated in both roots and leaves. Our results indicate a magnitude of drought stress effects reflected via repression of germination and seedling growth as well as adjustments in physiological functions at later growth stages, in a genotype depended manner. Among landraces, "751" and "746" showed better performance, as evidenced by higher seed germination and seedling This is a provisional file, not the final typeset article growth potential even at high stress levels (-0.47 and -0.73 MPa), whereas "747" was the most sensitive landrace to drought stress at both tested stages. In conclusion, our findings highlight the importance of squash landraces selection for the identification of elite genotypes with increased tolerance to drought stress.Οur findings contribute towards understanding the response of squash landraces to drought stress and further provide evidence regarding the tolerance ability of the genotypes under study at germination and seedling stage. The studied squash landraces exhibit considerable variation for drought tolerance traits, thus providing ground both for selecting appropriate landraces for cultivation under water deficit conditions and applying breeding approaches targeted at improving crop's drought tolerance. However, further studies are needed with a broader group of squash accessions that will help to valorize the existing variability through the selection of elite genotypes in targeted breeding programs.